On the Intersection of Science and Religion: A Critical Analysis of Abdulkarim Soroush’s Thought - Zamzami, Mukhammad; Gharamaleki, Ghorbanali Karimzadeh; Hosseinieskandian, Abdullah; A'la, Abd (Department of Religious Studies, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2022)
The idea of producing religious science is known not only in Iran and the Islamic world but also in the Western world. This idea has created movements in the Western world and the Islamic world in the field of science production, which are mainly divided into three perspectives. In the sources of science production, a group has given originality to naqlī (narrative) knowledge, a group to human knowledge and experimental sciences, and the third group confirmed both views and considered the way to acquire knowledge to be both intellect and narration. Abdulkarim Soroush is among those who have given originality to experimental sciences and knowledge in this field. In this article, an attempt is made to explain the nature of religious science with a descriptive-analytical method, examine and explain Soroush’s point of view, and state his bases and arguments in explaining this theory, and finally to criticize his point of view. Confusion of the two authorities of demonstration and confirmation, failure to provide a criterion for judging between religion and human knowledge in times of conflict, and the invalidity of generalizing historical evidence to all ages are some of the things that undermine the acceptance of Soroush’s theory.